Impact of Online Teaching and Learning on the UnderGraduate Students during the Pandemic. (International Journal of Food and Nutritional Sciences, 2022)
COVID-19 is a highly infectious disease caused by coronavirus 2 (SARS-CoV-2). It has originated in Wuhan city of China. The coronavirus triggered first phase in the form of nationwide lockdown in India which commenced on March 25, 2020. It has globally put, over 1.2 billion children out of the classroom. This situation challenged the educational system across the world and forced educators to shift to an online mode of teaching abruptly. Many academic institutions that were forced to transform entirely to online teaching and learning. Hence, there was distinctive rise in e-learning, whereby teaching is undertaken through digital platforms. The lack of digital tools is a major drawback amongst students, there is difficulty in understanding, social isolation and poor communication skills. The impact of the virus was so strong that online education became an omnipresent part of education, resulting in no further physical interaction of teachers with students. Due to the lockdown, students have not connected with the outer world resulting in lack of exposure. Since, students have been introduced to virtual platforms it made them well versed with technology with digital identity.On the other side of education i.e., the teachers, were greatly benefitted by teaching online, in such a way that it has increased their awareness of students' needs and methods to create engaging activities. Few teachers, realised it is easier to teach face-to-face after teaching online, while other teachers disagreed and faced challenges when returning to the face-to face classroom. The student teacher rapport has been affected very badly as the whole surrounding has drastically changed on account of unprecedented advent of pandemic. This research paper makes analysis of Impact of Online Teaching and Learning on the Under-Graduate Students during the Pandemic